ChemInform Abstract: Controllable Direct Arylation: Fast Route to Symmetrical and Unsymmetrical 4, 7‐Diaryl‐5, 6‐difluoro‐2, 1, 3‐benzothiadiazole Derivatives for Organic Optoelectronic Materials. Issue 15 (15th April 2014) - Zhang, Junxiang; Chen, Wayne; Rojas, Anthony J.; Jucov, Evgheni V.; Timofeeva, Tatiana V.; Parker, Timothy C.; Barlow, Stephen; Marder, Seth R.
Abstract An efficient protocol for the double symmetrical arylation using aryl bromides, one‐pot or sequential arylation using two different aryl bromides or monoarylation of difluorobenzothiadiazole is developed.